Germanium nanocrystals as luminescent probes for rapid, sensitive and label-free detection of Fe3+ ions1. Issue 12 (28th March 2015) - Carolan, Darragh; Doyle, Hugh
<x xml:space="preserve">Abstract</x> The optical properties of discrete sized Ge NCs and their application in the selective, sensitive and fast detection of Fe3+ ions in various water samples is reported.